Introduction to the digital format of the Philippine printing industry-an impact analysis and strategic prospective - Mercado, Rogel De Villa (University of the Philippines Diliman, 2009)
This project, "Introduction to the Digital Format of the Philippine Printing Industry-An Impact Analysis and Strategic Prospective", is a technology management paper focused on the dynamics-innovation, diffusion and adoption-of the digital technologies with the printing industry. This paper looks into the current situation of the Philippine Printing Industry and its adoption of the digital technologies. It aims to analyze and assess the impact of the digital technologies to the local industry and to provide recommendations or strategic prospective to be competitive. The first chapter is the introduction of the paper. It discusses the background, significance and the objectives of this project. It establishes the rationale on why the project is undertaken and the beneficiaries of the results of the project. The conceptual framework is discussed on the second chapter. The input-transformation-output framework will be used in understanding the current state of the Philippine Printing Industry and analyzing the impact of the digital technology to this framework. Technology management theories and concepts incorporated such as innovation, diffusion, adoption and acquisition of technology are also discussed in this chapter. The third chapter lengthily discusses the methodology employed by the proponent in executing the project. This chapter elaborates the research type, required data and the tools that will be used by the proponent. The proponent explains in this chapter the exploratory and predictive nature of this research being a pioneer in this topic. The sources of data are also outlined- the interview as the primary data and government statistical data, available studies and other literature as secondary data. Technology management concepts of innovation, diffusion and adoption and hierarchy of firm level technological capability are used as tools by the proponent on understanding the technological dynamics of digital technology in the printing industry.